Effect of Alkali Lignin on Heat of Fusion, Crystallinity and melting points of Low density polyethylene(LDPE), Meduim density polyethylene(MDPE) and High density polyethylene(HDPE) - Khalaf, Moayad (University of Thi-Qar Journal of Science, 2010)
Use of alkali lignin as a filler for polymers had been many advantage: non corrosive, low cost because (it source from black liquor which is waste from cooking of pulp) and used to improve the physical and mechanical properties of polymers. Alkali lignin added to three type of polyethylene (LDPE, MDPE and HDPE) in several concentrations (10-50% wt/wt).Thermal study by Differential Scanning Calorimetry (DSC) for this composites was studied ,its found that the heat of fusion ΔH and crystallinity decreased until 30% in composites of MDPE and HDPE then raised in 40% and decreased in 50% while It’s increased for LDPE composites until 20% then decreased in 50%. The melting points for HDPE composites with lignin were higher than MDPE and LDPE composites.